Market Equilibrium in a Model of a Planned Economy of the Soviet Type: A Proof of Existence and Results of Numerical Simulations - Feltenstein, Andrew (Review of Economic Studies, 1979)
Journal Article Market Equilibrium in a Model of a Planned Economy of the Soviet Type: A Proof of Existence and Results of Numerical Simulations Get access Andrew Feltenstein Andrew Feltenstein International Monetary Fund Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 4, October 1979, Pages 631–652, https://doi.org/10.2307/2297032 Published: 01 October 1979 Article history Received: 01 July 1976 Accepted: 01 July 1978 Published: 01 October 1979